Correlation between the immunological condition and the results ofimmunoenzymatic tests in diagnosing infectious mononucleosis - Tamaro, G.; Donato, M.; Princi, et al., T. (Acta Biomedica Atenei Parmensis, 2009)
Background and aim of the work: A symptom-based diagnosis of infectious mononucleosis is not sufficiently accurate, since some clinical symptoms of infectious mononucleosis are also detected in other virally induced diseases. Moreover, not all patients suffering from infectious mononucleosis show circulating atypical lymphocytes, which are considered characteristic of this disease. Therefore, when this disorder is suspected, serum analyses are carried out to detect the presence of certain immunoglobulins associated with infectious mononucleosis in the patient’s blood. The aim of this study was to evaluate the sensitivity and the specificity of a rapid test detecting heterophil antibodies in diagnosing infectious mononucleosis in a paediatric population. Methods: We considered 163 paediatric patients with suspected infectious mononucleosis and we tested their serums to detect heterophil antibodies (using an inexpensive and rapid test) and specific immunoglobulins directed against Epstein-Barr virus (EBV) (these assays are known to be characterized by high sensitivity and specificity, but are more expensive and time-consuming). Results: By comparing the results of the rapid test with those of the other assays, we found that the sensitivity of the first test was 61.8%, whereas its specificity was sufficiently high (about 90%). Conclusions: We show that, in paediatric patients, the detection of heterophil antibodies is not a very sensitive test, therefore the determination of immunoglobulins against specific antigens of EBV is recommended.